Contractarian approaches to intergenerational justice: paper presented at the Tinbergen Institute, Amsterdam, June 1996 and at the annual meeting of the European Public Choice Society, Prague, April 1997 - Hans-Peter Weikard (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 1997)
In modern political philosophy social contract theory is the most prominent approach to individual rights and fair institutions. According to social contract theory the system of rights in a society ought to be justified by reconstructing its basic features as a contract between the mutually unconcerned members of society. This paper explores whether social contract theory can successfully be applied to justify rights of future generations. Three competing views are analysed: Rawls's theory of justice, Hobbes's radical liberalism and Gauthier's bargaining framework based on the Lockean proviso.
urn:nbn:de:kobv:517-opus-8529
Keywords: D90; D63; 330